Correlation of Spinal Deformity Index and Bone Mineral Density in Postmenopausal Osteoporotic Women - Baha Çelik; Fikret Tüzün; Halime Toros; Şansın Tüzün; Önder Aydıngöz; Ülkü Akarırmak; Aynur Metin Terzibaşoğlu (Galenos Yayinevi, 2004)
Lumbar spine is the most frequently effected skeletal site by bone loss due to menopause in women. Therefore increased dorsal kyphosis and spinal deformity are the most common problems in postmenopausal women with spinal osteoporosis. The aim of this study was to evaluate the relationship between spinal deformity index (SDI) and bone mineral density in postmenopausal women with spinal osteoporosis.Fifty women aged 51-80 years were examined in the study. In all cases age, weight, height, body mass index, menopause duration and menopause age were examined. The mean age was 64.60+/-8.01. The spinal deformity index (SDI) was evaluated according to the Genant Method, 24 patients (48%) had mild deformation (Grade 1), 26 patients had moderate deformation (Grade 2). The mean age of cases in Grade 2 was significantly higher than Grade 1 (p<0.05). Both mean age and menopause duration were significantly higher in Grade 2 than Grade 1 SDI (p<0.05). There was no correlation between SDI degrees and height, weight, body mass index (BMI) and menopause age. There was no correlation between Grade 1 and 2 SDI and L1-4 BMD, trochanter BMD, total hip BMD. In patients with Grade 1 SDI, neck BMD was signficantly higher than Grade 2 SDI patients. In our study, spinal deformity index calculated with Genant Method was positively correlated with age and duration of menopause. In our cases, vertebral deformities were mild or moderate.